TRIPHALADI NIRUHA BASTI IN THE MANAGEMENT OF CHRONIC KIDNEY DISEASE - M Goud, Kiran; S Shirur, Basavaraj; K.N, Vinay Kumar; Mishra, Baidyanath (International Journal of Ayurveda and Pharma Research, 2015)
Kidneys are the organs that have numerous biological roles in maintaining the homeostatic balance of body fluids by removing wastes out of the body. Chronic Kidney Disease (CKD) has always remained a major area of concern since a long time as it leads to irreversible deterioration in renal function which classically develops over a period of years. CKD is considered when glomerular filtration rate (GFR) falls below 30 ml/min. The conventional approach of management includes dialysis and renal transplantation, which are not easily affordable. If still can afford it, these costs have to be borne for life time and where in the complication problems after a transplant may include post-operative complication, bleeding, infection, vascular thrombosis and transplant rejection. Therefore, exploration of a safe and alternative therapy is needed, which proves to be helpful in reducing the requirement of dialysis and in postponing the renal transplantation. Ayurveda highlights the significance of Trimarma viz., Sira, Hrudaya, and Basti which are to be protected, if not may lead to many trivial diseases and may turn fatal. Though Basti Marma is identified structurally as bladder, the entire functional aspect of renal system is to be considered among which functioning of Kidneys occupies the major place. If we consider CKD as the disease affecting Basti Marma, then Basti Karma can be adopted as the treatment of choice as it is told to be best for Marma Paripalana. In this regard, a study was designed to manage the conditions of chronic kidney disease with Triphaladi Niruha Basti administered in Kala basti pattern along with Shamana Aushadis. The study revealed that there is marked improvement in reducing the clinical and laboratory manifestations of CKD.